2018
DOI: 10.32598/ijt.12.3.511.1
|View full text |Cite
|
Sign up to set email alerts
|

Histopathological Study of Protective Effects of Honey on Subacute Toxicity of Acrylamide-Induced Tissue Lesions in Rats’ Brain and Liver

Abstract: Background: The therapeutic potential of honey is related to antioxidant activity against reactive oxygen species because it contains compounds such as polyphenols; therefore, we evaluated the potential protective effect of honey on subacute toxicity of ACR by histopathologic study on tissue lesions in rat. Methods: In Ferdowsi University of Mashhad, Mashhad, Iran, 2016, male Wistar rats were divided into 7 groups. To induce toxicity, ACR was injected (50 mg/kg for 11 d) to rats in 5 groups. In treatment group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…When chrysin (a polyphenol available in honey) was administered intraperitoneally in various dosages, it prevented cigarette smoke-induced inflammation by decreasing the inflammatory cytokines and myeloperoxidase activity by lowering the phosphorylation of p38 and ERK [ 39 , 40 ]. Honey protects rat testes from smoking-induced histological alterations and oxidative stress, according to several studies [ 41 , 42 ]. Honey considerably decreased the harmful effects of cigarette smoking on testicular structures and oxidative stress by lowering lipid peroxidation and restoring the antioxidant system [ 43 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…When chrysin (a polyphenol available in honey) was administered intraperitoneally in various dosages, it prevented cigarette smoke-induced inflammation by decreasing the inflammatory cytokines and myeloperoxidase activity by lowering the phosphorylation of p38 and ERK [ 39 , 40 ]. Honey protects rat testes from smoking-induced histological alterations and oxidative stress, according to several studies [ 41 , 42 ]. Honey considerably decreased the harmful effects of cigarette smoking on testicular structures and oxidative stress by lowering lipid peroxidation and restoring the antioxidant system [ 43 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…The chemical structure of ACR and its metabolic conversion ability make it able to react with various cells. Various studies of the effects of ACR on various tissues such as the testis, liver, kidney, and brain have been investigated and it has been observed that It has led to changes in the tissues of the organs [6][7][8]. ACR affects especially the enzymatic and endocrine function of the testis [9] ACR causes cystic changes in the ovary and structural changes in the granulosa layer of the follicles.…”
Section: Introductionmentioning
confidence: 99%